Removal of Bisphenol A by Soybean Hulls Peroxidase - Jiang, Xiadong; Zheng, Huaili (Asian Journal of Chemistry, 2013)
The soybean hulls peroxidase is known to remove chemical compounds from aqueous pollutant solutions. This study evaluates the potential of the soybean hulls peroxidase in the degradation of aqueous bisphenol A. Soybean hulls peroxidase (EC 1.11.1.7) was extracted and purified from soybean hulls. The molecular weight of the soybean hulls peroxidase is 37 kDa, determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Some physicochemical properties of the native enzyme, such as pH and temperature, were evaluated in order to determine the optimum conditions for the enzyme performance. We found the activity of soybean hulls peroxidase was higher at pH 5.0 and 50 ºC. For the removal of bisphenol A tested, the initial amount of H2O2 and the soybean hulls peroxidase were detected. The results indicated that the degradation of bisphenol A was over 80 % at soybean hulls 2 g/25 mL. This study verifies the viability of the use of the soybean hulls peroxidase in the biodegradation of the simulated bisphenol A pollution.